“Artisti in Russia” by Ettore Lo Gatto: Transnational Art and History Studies during the Dictatorship in Italy and the USSR in 1920–1940s - Vyazemtseva, Anna G. (Actual Problems of Theory and History of Art, 2021)
The article examines a book called “Artists in Russia” published in Italy in 1934–1943 by the Italian slavist Ettore Lo Gatto as an attempt to do a comparative transnational research. This approach though relevant for the history of art and architecture today was new in the first half of the 20th century, when the science rather considered national schools, than the question of mutual influence. Lo Gatto’s work made part of the series “Italian Genius Abroad” and aimed to testify to the dominance of Italian culture over other world cultures in the framework of the propaganda of fascism; it did not set the direct task of studying the migration of Italian masters, its conditions and the results of the interaction with other national schools. As a propaganda project of the Mussolini regime, ‘Artists in Russia’, however, simultaneously became the first comprehensive work on Italian masters in Russia, and, albeit unintentionally, turned out to be one of the first attempts to create an “international” art history and to study intercultural contamination between two countries. Based on documents from the archives of the Italian Ministry of Foreign Affairs, the article describes the process of the research, analyzes the work of Lo Gatto as one of the first studies of artistic migration, and shows an episode of interaction between art historians of the two countries under the conditions of dictatorship and ideological, and then military conflict making a contribution to the history of international relations of the first half of the 20th century.The reported study was funded by RFBR and CNRS according to the research project № 21-512-15002.
Keywords: Ettore Lo Gatto; transnational history; diplomatic relations; Italian Slavistics; Italian architects in Russia; cultural exchange; Russia – Italy; international relations of USSR; international relations of Italy in 20th century